Plasma levels of D-dimer and fibrin degradation products correlate with bullous pemphigoid severity: a cross-sectional study - Sijia Wang (Nature Portfolio, 2021)
Abstract Bullous pemphigoid (BP), the most frequent blistering dermatosis in the elderly, is associated with increased mortality. The severity of BP can be assessed by detecting the anti-BP180 immunoglobulin G (IgG) concentration, but the lab test is not available in many community clinics. BP patients are usually in a hypercoagulable state with increased levels of D-dimer and fibrin degradation products (FDPs). We aimed to evaluate the use of D-dimer and FDPs in assessing BP severity. We compared the levels of plasma D-dimer, plasma FDPs, eosinophil counts, eosinophil cationic protein, and serum anti-BP180 IgG concentration between 48 typical BP patients and 33 Herpes zoster (HZ) patients (control group). Correlational analyses were conducted to determine the relationships between the lab values and common BP severity markers. The plasma D-dimer and FDP levels were higher in BP patients than in HZ controls (D-dimer: 3297 ± 2517 µg/L vs. 569.70 ± 412.40 µg/L; FDP: 9.74 ± 5.88 mg/L vs. 2.02 ± 1.69 mg/L, respectively, P < 0.0001). Significant positive correlations were found between D-dimer/FDP levels and BP severity markers (i.e. anti-BP180 IgG concentration [D-dimer: r = 0.3928, P = 0.0058; FDP: r = 0.4379, P = 0.0019] and eosinophil counts [D-dimer: r = 0.3625, P = 0.0013; FDP: r = 0.2880, P = 0.0472]) in BP patients. We also found an association between FDP and urticaria/erythema lesions (r = 0.3016, P = 0.0372), but no other BPDAI components. In 19 BP patients with complete remission after systemic glucocorticoid treatment, D-dimer and FDP levels decreased post-therapy (D-dimer: 5559 ± 7492 µg/L vs. 1738 ± 1478 µg/L; P < 0.0001; FDP: 11.20 ± 5.88 mg/L vs. 5.13 ± 3.44 mg/L; P = 0.0003), whereas they did not in BP patients with treatment resistant. Plasma D-dimer and FDP are convenient markers to evaluate BP severity assistant on BPDAI and eosinophil counts. FDP is also helpful for inflammatory lesions in BP patients.